Microphenophases on some junebearing strawberry varieties in region of Skopje - Ana Selamovska, S. Kratovalieva, S. Petrovic, M. Dimitrijevic (Bulgarian Journal of Agricultural Science, 2013)
This paper gives an overview of the results from the microphenophases on junebearing strawberry varieties: Pocahontas, Evita, Marmolade, Belrubi and Elsanta in Skopje region, Republic of Macedonia. The beginning of the flower bud differentiation among the studied strawberry varieties is, on average, during the first half of August when the day lasts for 13.5-14 hours. The calyx is formed the second half of September, stamens during the first half of October, and the pistils during the second half of October. Archesporial tissue and meiosis are formed in November. The microspores are formed in December. Pocahontas variety has earliest flower bud initiation (FBI), followed by Evita, Marmolade and Belrubi. Elsanta variety has the latest FBI. The higher temperatures and a photoperiod (duration of sunshine)have positive influence on early FBI.
Keywords: strawberry, differentiation, flower buds, microphenophases